2016
DOI: 10.1111/jnc.13765
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of antibodies on retinal ganglion cells in an adolescent retina organ culture

Abstract: Glaucoma, a neurodegenerative disease, is characterized by a progressive loss of retinal ganglion cells (rgc). Up- and down-regulated autoantibody immunoreactivities in glaucoma patients have been demonstrated. Previous studies showed protective effects of down-regulated antibodies [gamma (γ)-synuclein and glial fibrillary acidic protein [GFAP]) on neuroretinal cells. The aim of this study was to test these protective antibody effects on rgc in an organ culture model and to get a better understanding of cell-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 77 publications
(82 reference statements)
0
33
0
Order By: Relevance
“…Another previous study showed that the gliosis may impede the migration and integration of transplanted photoreceptors [ 21 ]. Additionally, in vitro studies indicated that anti-inflammation treatment including rapamycin not only reduced local inflammation and proliferation, but also provided a protective effect of neurons [ 22 , 23 ]. Consistently, with weekly intravitreous rapamycin injection, the slight glial reaction induced by retinal tack was notably improved in present surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study showed that the gliosis may impede the migration and integration of transplanted photoreceptors [ 21 ]. Additionally, in vitro studies indicated that anti-inflammation treatment including rapamycin not only reduced local inflammation and proliferation, but also provided a protective effect of neurons [ 22 , 23 ]. Consistently, with weekly intravitreous rapamycin injection, the slight glial reaction induced by retinal tack was notably improved in present surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies changes detected include elevated levels of antibodies against α -fodrin, glutathione-S-transferase, spectrin, and Heat Shock Protein (HSP) 70 and decreased levels of antibodies against α B crystalline, vimentin, Glial Fibrillary Acidic Protein (GFAP), and ϒ-Synuclein [ 102 – 105 ]. In vitro studies have shown that antibodies against ϒ-Synuclein and GFAP possess direct and indirect (through Mϋller cells) protective effect on the retinal ganglion cells [ 106 ]. Results from clinical studies revealed altered immunoreactivities against retina and optic nerve in sera and aqueous humour of glaucoma patients which indicates a role of autoimmunity in glaucomatous neurodegeneration and retinal ganglion cells death.…”
Section: New Targets For Iop-lowering and For Iop-independent Thermentioning
confidence: 99%
“…In accordance with previous results, immunohistochemical analysis revealed a protective effect of anti-γ-synuclein and anti-GFAP antibodies on RGC survival (Figure 3) and demonstrated the uptake of γ-synuclein antibodies, as well as the binding of GFAP antibodies to the cell membrane of Müller cells. 47 Furthermore, mass spectrometric results showed Eye increased levels of glutamine synthetase in antibodytreated retinal explants. Glutamine synthetase is expressed exclusively in Müller cells and serves as a specific Müller cell marker.…”
Section: Neuroprotective Effects Of Antibodies On Retinal Explantsmentioning
confidence: 99%
“…These findings suggest that anti-GFAP and anti-γ-synuclein antibodies have a protective effect on RGC which seems to be the result of reduced stress levels in the retina. 47 Possibly the absence or the loss of some autoantibodies in glaucoma patients (eg, anti-GFAP) reflects a loss of natural protective autoimmunity, thus encouraging neurodegenerative processes and making the RGC more vulnerable for stress factors. 12…”
Section: Neuroprotective Effects Of Antibodies On Retinal Explantsmentioning
confidence: 99%